2019
DOI: 10.1007/s10147-019-01578-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of alkaline phosphatase in hormone-sensitive prostate cancer: a systematic review and meta-analysis

Abstract: Purpose To assess the prognostic value of alkaline phosphatase in patients with hormone-sensitive prostate cancer. Methods A systematic review and meta-analysis was performed using the PUBMED, Web of Science, Cochrane Library, and Scopus in April 2019 according to the Preferred Reporting Items for Systematic Review and Meta-analysis statement. Studies were deemed eligible if they compared hormone-sensitive prostate cancer patients with high vs. low alkaline phosphatase to determine its predictive value for ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
(37 reference statements)
0
22
1
Order By: Relevance
“…Besides, alkaline phosphatase (ALP) is enriched in kidney, bile duct, and liver [9]. Studies have shown that serum ALP is a useful marker of tumor growth and metastasis [10][11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, alkaline phosphatase (ALP) is enriched in kidney, bile duct, and liver [9]. Studies have shown that serum ALP is a useful marker of tumor growth and metastasis [10][11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…This also partly explained why cancer patients with elevated ALP were more likely to have a poor prognosis. Meanwhile, cancer patients with elevated ALP would benefit more from intensive therapy than standard therapy [ 33 ]. Furthermore, ALP was also expressed in cancer cells, which could regulate tumor growth [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The timely intervention of ALB in patients with low AAPR can increase AAPR, thereby correcting nutrition and improving treatment effectiveness. Meantime, patients with low AAPR might need more extra radiotherapy or chemotherapy, due to increased ALP might reflect micrometastases [33].…”
Section: Plos Onementioning
confidence: 99%
“…Beside that, alkaline phosphatase (ALP) is enriched in kidney, bile duct, and liver [9]. Studies have shown that serum ALP is a useful marker of tumor growth and metastasis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%